The Impact of Brand Image and Product Quality on Purchasing Decisions - Dirwan Dirwan; Ahmad Firman (Jurnal Manajemen Bisnis, 2023)
This study aims to test and analyze the effect of brand image and product quality on purchasing decisions for Lenovo brand laptops at the Nobel Institute of Technology and Business in Indonesia. Sampling in this study used non-probability sampling techniques because the chances of an element being selected as a subject are unknown. So the researcher set 198 samples. The data source of this research is primary data, namely data obtained from the results of distributing questionnaires to all respondents. The statistical method used to test the hypothesis uses the help of the SPSS application. The results showed that brand image influences purchasing decisions for Lenovo brand laptops at the Nobel Institute of Technology and Business in Indonesia, so it is stated that the first hypothesis is accepted. And product quality affects purchasing decisions for Lenovo brand laptops at the Nobel Institute of Technology and Business in Indonesia. This identifies that product quality is essential for purchasing decisions for students